Leading Sector Analysis of Central Java Province - Marpaung, Grace Natalia; Karisma, Dewi; Asrianti, Nurul; Aprilia, Rizka Nanda (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The value of regional economic growth plays an important role in encouraging regional development. The economic potential of Central Java Province is so large because it is supported by the manufacturing industry and its natural preservation. This study uses a descriptive quantitative approach using Location Quotient analysis tools and Shift Share analysis by processing time series data in the form of constant National GDP and constant GRDP in Central Java in 2017-2021. The results show that the leading industries in Central Java are manufacturing, educational services, accommodation and catering, wholesale and retail, and automobile and motorcycle maintenance, and construction. Industries that have competitiveness are mining and quarrying, electricity and gas procurement, construction, wholesale and retail, and automobile and motorcycle maintenance, accommodation andcatering, information and communication, business services, and educational services.